(untitled) (Archives of Criminology, 2023)
The aim of this paper is to examine South-eastern European students’ experiences being victims of criminal offences against property or being witnesses to criminal offences against property; to compare the extent to which students reported the crimes they were victims of or had witnessed; and to examine their willingness to report a theft of property of minor value (bicycle theft) in a hypothetical victimization situation, considering their country of residence and previous experience of reporting. The survey was conducted by an online survey in seven countries of South-eastern Europe (Bosnia and Herzegovina, Montenegro, Croatia, Hungary, Northern Macedonia, Slovenia, and Serbia) on a sample of 1,419 students. The results indicate that a large proportion of property crimes go unreported, although most students are willing to report them.